Analysis of the Twisting Tension in the Direct-Twisting Machine and the Fitting Model Based on the Experimental Data - Shunqi Mei; Mengying Zhang; Di Qi; Liye Yang; Qiao Xu; Ming Zhang (Applied Sciences, 2022)
The tension of the balloon yarn in the direct-twisting machine affects the yarn breakage and balloon shape, which in turn affects the energy consumption and yarn productivity of the direct-twisting machine. At present, research on the balloon tension of an industrial yarn direct-twisting machine is very rare, both in China and abroad. In this regard, this paper establishes a theoretical model for balloon yarn tension during the yarn twisting process of an industrial yarn direct-twisting machine based on yarn balloon kinematics. The experiment of the yarn balloon tension of the direct-twisting machine under different yarn fineness and different spindle angular speed is carried out. The influence of the angular speed of the spindle, the yarn fineness, and other factors on the tension of the balloon yarn in the direct-twisting machine is investigated. By using mathematical statistics and regression analysis methods, the fitting equations of the yarn balloon tension of the direct-twisting machine are established. The research results show that the relationship between the balloon yarn tension of the direct-twisting machine, the angular velocity of the spindle, and the yarn fineness can be fitted by a quadratic polynomial. The predicted value of balloon yarn tension based on the fitted equation has a small relative error compared to the measured value, and the prediction result is more reliable and accurate. This paper contributes specifically by adding to the understanding of how to model the yarn tension for the specific machine and the range of the test. It also contributes to the generical methodology on how to develop such a model.